Climacteric syndrome and magnesium (literature review) - V N Prilepskaya; A N Mgeryan; E A Mezhevitinova (IP Berlin A.V., 2018)
Magnesium is one of the most important trace elements necessary for the life of the human body. It supports the normal exchange of proteins and nucleic acids (DNA and RNA), reduces spasm of the arteries, both peripheral and coronary, prevents the formation of blood clots, relaxes the uterus with hypertension, restores heart rhythm with tachycardia, contributes to the normal course of pregnancy, etc. Magnesium deficiency has a negative impact on health, especially in women in the menopause. Hypomagnesemia exacerbates the course of the main clinical manifestations and conditions characteristic of climacteric syndrome, and therefore the use of magnesium preparations in this category of patients will improve their health and quality of life.